Why Exhibit at an Exhibition - Nataraj, Bharati; Anitha Prasad, T. (Indian Journal of Marketing, 2006)
Nothing is constant but change!Markets and their importance are no exception to this principle. Marketing and advertising today have become as important as manufacturing and production due to the increasing competition and awareness among the consumers. In the present day scenario, where the consumer is the king, it has become very important for the marketers to interact with the consumers, study their needs, explain the features of their products and convince the consumers about the benefits of their products. All this is to maintain regular customers and build an image and also have a good product positioning.